Baby Girl with Mesoblastic Nephroma Kidney Tumor (NM) - Dian Komaladewi; Freedy LP Tambunan; Edwam Akbar (Universitas Islam Bandung, 2022)
AbstractBackground: Mesoblastic nephroma (NM) is the most common benign kidney tumor in infants, mostly occurring in the first six months of life; it is still very rare. These tumors are almost always diagnosed in children under two years of age. Radical nephrectomy as curative therapy.Case presentation: We report the case of a 22-day-old baby girl with complaints of enlarged abdomen which was known since the patient was born. The patient was born to G3P0A0 mother, 9 months of gestation, through normal delivery. Babies are born crying immediately. Birth weight 3100 grams. Abdominal examination, convex, normal bowel sounds, soft palpation, palpable solid mass on both flank, well defined, fixed, painless, size 15x15x10 cm. Renal ultrasound examination revealed bilateral renal masses ec DD/ Wilm's tumor, mesoblastic nephroma. Abdomen CT examination with contrast revealed a solid mass in the upper to lower abdomen bilaterally obliterating both kidneys, pressing the intestines to the middle abdomen, superiorly pressing the liver and spleen, anteriorly attached to the abdominal wall, posteriorly attached to the vertebral bodies ec DD/ mesoblastic nephroma, Wilm's tumor. Anatomical pathology examination revealed benign cystic lesions on both kidneys bilaterally.Conclusion: Radiological imaging has a major role in establishing the diagnosis of NM, so it will assist in the selection of fast and appropriate treatment.